Effects of virtual Reality-Based Training and aerobic training on gaming disorder, physical activity, physical fitness, and anxiety: A randomized, controlled trial - Maden, Çağtay; Bayramlar, Kezban; Arıcak, Osman T.; Yağlı, Naciye Vardar (Elsevier Ltd, 2022)
Background and aim: The effects of physical activity and exercise on gaming disorder severity in individuals with gaming disorder are unknown. The present study aimed to address the empirical gap in the current literature by comparing the effects of virtual reality-based training (VRT) and aerobic training (AT) exercise programs on gaming disorder severity, physical activity, physical fitness, and anxiety versus control group. Materials and methods: Forty-four young male adults (18–28 years) with gaming disorder and a sedentary lifestyle were included in the study. The primary outcomes of the study were changes in gaming disorder severity and physical activity, and secondary outcomes included changes in physical fitness and anxiety levels. The participants were randomly assigned to VRT (n = 15), AT (n = 14) and control (n = 15) groups. Training sessions were performed at 50–70% of the maximal heart rate. Exercise programs consisted of 6 weeks of training 3 times a week for 30 min. Results: There was a decrease in the severity of gaming disorder as well as an increase in the level of physical activity in the VRT and AT exercise groups compared to the control group. In addition, a reduction was observed in the gaming time and sedentary time in both exercise groups versus control group. VRT group experienced greater improvements in physical fitness parameters than the AT group. Conclusion: VRT and AT were effective in reducing gaming time and the severity of gaming disorder in individuals with gaming disorder. The therapeutic effects of VRT and AT can be used for reducing the severity of gaming disorder. © 2022 Elsevier Ltd
Keywords: aerobic exercise; anxiety; exergame; gaming disorder; physical activity; physical fitness